A survival case of a young adult patient with ST-elevated myocardial infarction with high levels of lipoprotein(a). Issue 6 (June 2019) - Hiraiwa, Hiroaki; Morimoto, Ryota; Okumura, Takahiro; Arao, Yoshihito; Oishi, Hideo; Kato, Hiroo; Yamaguchi, Shogo; Kuwayama, Tasuku; Haga, Tomoaki; Yokoi, Tsuyoshi; Kondo, Toru; Watanabe, Naoki; et al.
Abstract: A 23-year-old Japanese man presented to a nearby hospital with a complaint of chest pain. In terms of the risk factors for cardiovascular events, there were no abnormal findings in past medical examinations and no smoking history. The 12-lead　electrocardiogram revealed ST-elevation in V1-V6, I, and aVL, and he was diagnosed with acute myocardial infarction. Emergency coronary angiography findings revealed total occlusion of the left main trunk and collateral vessels from the right coronary artery to the left anterior descending artery. He underwent emergency percutaneous coronary intervention and placement of drug-eluting stent under the support of venoarterial-extracorporeal membrane oxygenator (VA-ECMO). On day 8 after the onset, transthoracic echocardiography revealed that cardiac function improved with left ventricular ejection fraction from 10% to 20% and VA-ECMO was successfully removed. Alternatively, laboratory findings revealed abnormally high levels of serum lipoprotein(a) [Lp(a), 74 mg/dL] despite the normal levels of low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglyceride. In addition, computed tomography angiography revealed atherosclerosis and stenosis of internal and external carotid arteries, subclavian artery, and renal artery. The abnormally high levels of serum Lp(a) could influence systemic atherosclerosis as well as the onset of myocardial infarction in our young adult patient. <Learning objective: This was a rare survival case of a young adult patient with acute extensive myocardial infarction owing to plaque rupture of the left main trunk. Additionally, he had atherosclerosis of the whole body, including the carotid artery, subclavian artery, and renal artery. Blood test results revealed abnormally high levels of serum lipoprotein(a) [Lp(a)] despite the normal levels of low-density lipoprotein cholesterol. Lp(a) could strongly influence coronary atherosclerosis and myocardial infarction.>